Stent thrombosis with bioabsorbable polymer drug-eluting stents: insights from the Food and Drug Administration database. Issue 7 (November 2017) - Khan, Abdur R.; Tripathi, Avnish; Farid, Talha A.; Abaid, Bilal; Bhatt, Deepak L.; Resar, Jon R.; Flaherty, Michael P.
Abstract : Background: SYNERGY, a bioabsorbable polymer-based, everolimus-eluting stent (BP-DES), recently received regulatory approval in the USA for use in percutaneous coronary interventions. Yet, information on the safety of BP-DES in routine clinical practice is limited. Our aim was to compare the safety of the recently approved BP-DES with current durable polymer drug-eluting stents (DP-DES) by analyzing adverse events, namely, stent thrombosis (ST), reported to the Manufacturer and User Facility Device Experience (MAUDE) database. Materials and methods: The MAUDE database requires nationwide mandatory notification for adverse events on devices approved for clinical use. This database was searched for adverse events reported between 1 October 2015 and 25 December 2016, encountered after the placement of either BP-DES or DP-DES. Only those adverse events were included where the exposure period to the stents was comparable after the index procedure. Of all the adverse events reported, the event of interest was ST. Results: A total of 951 adverse events were reported. ST occurred in 48/951 of all events, 31/309 and 17/642 when BP-DES or DP-DES were used, respectively ( P =0.00001). Of the 31 ST events with BP-DES, 68% (21/31) occurred within less than or equal to 24 h of the index procedure and 52% (16/31) occurred within less than or equal to 2 h. Conclusion: Our results raise the possibility of an increased risk of ST, particularly early ST (within 24 h), with the recently approved BP-DES. However, because of the inherent limitations of reporting within the MAUDE database, these data merely highlight a potential need for additional surveillance and randomized trials to assess further the safety of the bioabsorbable platform.